Discovery of a parallel family of euglenatide analogs in Euglena gracilis - Ahmed H. Elbanna; Xinhui Kou; Dilip V. Prajapati; Surasree Rakshit; Rebecca A. Butcher (Natural Products and Bioprospecting)
Abstract The euglenatides are a family of hybrid polyketide-nonribosomal peptides produced by the unicellular algae Euglena gracilis. These compounds have antiproliferative activity against fungal pathogens and mammalian cancer cell lines. Analysis of E. gracilis extracts revealed that the algae produce not only the euglenatides, but also a corresponding family of analogs that have the same molecular weights as the euglenatides, but are lacking the characteristic triene chromophore. In comparison to the euglenatides, the activity of these analogs is greatly reduced in a mammalian cytotoxicity assay, indicating that the triene is critical to the biological activity of the euglenatides. Graphical abstract